Day 2 Tue, September 29, 2015 2015
DOI: 10.2118/175101-ms
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Hydrocarbon Permeability After Hydraulic Fracturing: Laboratory Evaluations of Shut-ins and Surfactant Additives

Abstract: Fracturing fluid loss into the formation can potentially damage the hydrocarbon production in shale or other tight reservoirs. Well shut-ins are commonly used in the field as a way to dissipate the trapped water into the matrix near fracture faces. Borrowing from ideas in chemical enhanced oil recovery (CEOR), surfactants can be potentially used to reduce the impact of fracturing fluid loss on hydrocarbon permeability in the matrix as well. Unconventional tight reservoirs can differ significant from one anothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…However, gel residuals can block fractures and pores at fracture faces, thus impeding the flow of hydrocarbon [23][24][25]. Besides gel residuals, water can imbibe rock matrix and cause phase trapping, which reduces hydrocarbon permeability due to multiphase flow [26][27][28][29]. Formation damage due to drilling and fracturing fluids is likely different in the low-permeability sandstone with well-developed natural fractures.…”
Section: Introductionmentioning
confidence: 99%
“…However, gel residuals can block fractures and pores at fracture faces, thus impeding the flow of hydrocarbon [23][24][25]. Besides gel residuals, water can imbibe rock matrix and cause phase trapping, which reduces hydrocarbon permeability due to multiphase flow [26][27][28][29]. Formation damage due to drilling and fracturing fluids is likely different in the low-permeability sandstone with well-developed natural fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Ibrahim and Nasr-El-Din have recently even conducted similar experiments in tight sandstones (0.23 mD) and in Marcellus shales (3.16 nD) to show similar behavior of regained permeability to gas, as discussed above. Similarly, for an oil/water system in a low-permeable water-wet rock (3–10 mD), the studies performed by Liang and co-workers have also demonstrated the migration of water-block phenomenon using high-resolution CT-scans. Liang et al even concluded that for the case of an oil-wet rock, the water-block at the fracture–matrix interface does not exist but rather the end-point relative permeability for oil is subdued at the residual saturation of water due to the capillary entrapment of water in the bulk of the pore space and not along the walls of the pore space.…”
Section: Introductionmentioning
confidence: 92%
“…The large hydraulic pressure difference between the shale matrix and the fracture primarily results in fluid seepage inside the matrix and the recovered fluid is mostly formation water . Furthermore, spontaneous imbibition due to capillary pressure and the large osmotic potential due to the high-salinity contrast between the fracturing fluid and connate water also contributes to substantial loss of injected fluid in the reservoir.…”
Section: Evolution Of Shale Flow Channels Due To Reactive Transportmentioning
confidence: 99%
“…The component of the shale porosity present in the organic matter is assumed to be oil-wet, while interdetrital porosity tends to be more water-wet. The lost fluid has the tendency to change the surface wettability of the shale pores from oil-wet to water-wet. ,, The water phase in the micropores can become trapped due to the change in capillary pressures , or as a result of forming a connected hydrocarbon-phase ganglia that leaves the water-phase trapped near the water-wet pore surface (Figure ); this ultimately reduces the hydrocarbon recovery. , Multiple processes including heat and surfactant treatment have been proposed to mitigate this damage and enhance hydrocarbon recovery.…”
Section: Evolution Of Shale Flow Channels Due To Reactive Transportmentioning
confidence: 99%